ANALISIS PENGARUH LITERASI KEUANGAN, KESADARAN KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU MENABUNG (STUDI PADA MAHASISWA UNPRI) - San Fredo Munthe; Natasya Pebrina Silaen; Maya Sabirina Panggabean; Dewi Nurmasari Pane (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of financial literacy, financial awareness, and financial attitude on saving behavior among students of Universitas Prima Indonesia. Saving behavior is one form of financial management that is important for students in preparing their financial condition for the future. However, many students still exhibit consumptive behavior and lack saving habits. Therefore, it is necessary to understand the factors that influence students’ saving behavior. This study employed a quantitative approach using a survey method. The population in this study consisted of active students at UNPRI, with a sample of 133 respondents selected using purposive sampling techniques. Research data were collected through questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results showed that partially, financial literacy had a positive and significant effect on saving behavior with a significance value of 0.006 < 0.05. Financial awareness also had a positive and significant effect on saving behavior with a significance value of 0.004 < 0.05. Furthermore, financial attitude had a positive and significant effect on saving behavior with a significance value of 0.000 < 0.05. Simultaneously, financial literacy, financial awareness, and financial attitude significantly influenced saving behavior with an F-count value of 54.949 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.551 indicates that the independent variables were able to explain 55.1% of saving behavior, while the remaining percentage was influenced by other variables outside this study. Based on the research results, it can be concluded that improving financial literacy, financial awareness, and positive financial attitudes can encourage students to develop better saving behavior.